Essential oils in androgenetic alopecia management: An integrative review - Viveiros, Elenise Penha; Carvalho, André Luis Menezes; Lopes, Talissa Brenda de Castro; Ramos , Igor Frederico da Silveira; Alves, Paula Natanielle Nunes (Seven Editora, 2023)
The present study aims to present which essential oils (OEs) have published scientific studies on their action on hair growth and potential use in the management of androgenetic alopecia (AGA). The searches were conducted between May and June 2021, in the electronic databases PubMed, Science Direct, and VHL, using the descriptors "androgenetic alopecia", "alopecia", "hair loss", "hair growth", "essential oil",  "volatile oil" and "aromatherapy". In vitro and in vivo clinical studies were found with the OEs of the following species: Artemisia argyi, Angelica sinensis, Cananga odorata, Cedrus atlantica, Chamaecyparis obtusa, Laurus nobilis, Mentha piperita, Myrtus communis, Platycladus orientalis, Pimenta racemosa, Pogostemon patchouli     ,  Rosmarinus officinalis, Salvia officinalis, Salvia sclarea, Thymus satureioides and Zizyphus jujube,  alone or together with other vegetable oils and compounds. Research has shown that EOs stimulate hair growth by increasing microcirculation in the follicles, reducing scalp inflammation, or increasing the expression of growth factors. After reviewing the literature, it was concluded that there are several promising botanical ingredients for the treatment of alopecias, but there are still few solid and well-conducted clinical trials concerning AGA. Therefore, more studies need to be conducted for an effective evaluation of natural and complementary treatment options that better serve patients. DOI:https://doi.org/10.56238/devopinterscie-161